Factors Determining Consumer Purchase Intention and Willingness to Pay of Eco-Fashion Products - Wardana, Dhimas Sadewa; Fadhilla, Hanifa Nur (LifeSciFi, 2026)
The fashion industry involves the design, production, distribution, marketing, and sale of clothing for men, women, and children, including everyday wear. This study aims to examine the effects of environmental concerns and altruism on eco-fashion purchase intention, as well as the impact of purchase intention on E-WOM and willingness to pay premium prices, including the mediating role of E-WOM in the relationship between eco-fashion purchase intention and willingness to pay premium prices. The study employed a quantitative approach and involved 174 respondents from the Special Region of Yogyakarta who were familiar with environmentally friendly industries, particularly eco-fashion, selected using purposive sampling. This findings, environmental concern and altruism were found to have significant effects on eco-fashion purchase intention. Eco-fashion purchase intention, in turn, significantly influenced both Electronic Word of Mouth (E-WOM) and willingness to pay a premium price. E-WOM had a significant effect on willingness to pay a premium price. Both direct and indirect effects were identified, with the direct effects demonstrating a greater magnitude than the indirect effects. These results imply that strengthening environmental awareness and prosocial values can enhance consumers’ willingness to support eco-fashion products at premium prices.